Influence of Sports Intervention on the Mental Health of College Students in the Background of COVID-19 :A Systematic Review - Yang, Yi; Wu, Changhong; Sun, Liang; Wang, Chuanqiushui; Luo, Jiong (Quality in Sport, 2024)
Objective: This review aims to understand the mental health status of college students during the popularity of covid-19, and explore the impact of sports intervention on College Students’ mental health and its path mechanism through a literature review. Methods: According to PRISMA 2020 guidelines, this paper searched the literature on the Sports College Students’ Mental Health from 2019 to 2022 in PubMed, web of science, CNKI, and dimensional spectrum database. Results: 64 research papers were included for comprehensive analysis. Conclusions: Sport interventions as an important means for the regulation of the development of the mental health of the college students. Sport intervention improves cognitive functioning, emotional state, interpersonal relationships, and self-efficacy in college students and is an important strategy for dealing with public health emergencies. Sport intervention therapy is recommended as one of the important means to prevent mental health problems among college students.